Multifunctional Hybrid Silica Nanoparticles with a Fluorescent Core and Active Targeting Shell for Fluorescence Imaging Biodiagnostic Applications. Issue 27 (14th August 2015) - Santiago, Ana M.; Ribeiro, Tânia; Rodrigues, Ana S.; Ribeiro, Bruno; Frade, Raquel F. M.; Baleizão, Carlos; Farinha, José Paulo S.
Abstract: We prepared hybrid nanoparticles with a brightly fluorescent silica core and a biocompatible thermoresponsive polymer shell containing tumor‐targeting folic acid (FA) groups. The silica core has a perylenediimide fluorescent dye anchored covalently to the structure for traceability and bioimaging applications. The polymeric shell was synthesized by reversible addition–fragmentation chain‐transfer (RAFT) polymerization to guarantee the homogeneous size of the particle shell. The shell is composed of copolymer chains with one block of oligo(ethylene glycol)methacrylate and 2‐(2′‐methoxyethoxy)ethylmethacrylate with another block of the reactive monomer N ‐acryloxysuccinimide (NAS). The NAS groups were used to covalently attach a large amount of amino‐functionalized FA to the particle shells to provide active targeting properties towards cancer cells and tissues. The targeting capability of the folate‐containing nanoparticles was evaluated against NCI‐H460 tumor cells, which overexpress folate receptors. The nanoparticles with FA show a higher uptake efficiency compared to that of the equivalent nanoparticles without FA. This result validates the imaging capabilities and active targeting efficiency of our nanoparticles, an important step towards the goal of developing vehicles for precision drug delivery systems that combine therapeutic and diagnostic (theranostic) functionalities with large drug payloads, active targeting, and stimuli‐activated drug release. Abstract : We prepare hybrid nanoparticles with a brightly fluorescent silica core and a biocompatible thermoresponsive polymer shell containing a large amount of folic acid (FA) groups. The active cancer‐targeting properties of the FA are evaluated against NCI‐H460 tumor cells. The FA‐loaded nanoparticles internalize faster and in larger amounts than control counterparts without FA.